Analisis Faktor yang Berkontribusi dalam Pengembangan Wisata Halal dari Sudut Pandang Wisatawan di Jabodetabek - Eria Putri, Angghina; M Munandar, Jono (Jurnal Manajemen dan Organisasi, 2023)
Halal product trends are expanding from food to lifestyle, namely halal tourism. The development of halal tourism is driven by the large Muslim market in the world. Indonesia as the country with the largest Muslim population. The halal tourism authority, CrescentRating, awards Indonesia as the first best halal tourist destination in the OIC category. Jakarta is the fourth best halal tourist area in Indonesia, which in its development has a coordination chain with the surrounding areas, namely Bogor, Depok, Tangerang and Bekasi. Jabodetabek contributes greatly to the country's economy so that there is a need for the development of tourism in Jabodetabek. Therefore, it is necessary to adjust the needs of tourists in order to increase tourist attraction. This study aims to identify the characteristics of tourists and analyze the factors that contribute to the development of halal tourism through 46 indicators of halal tourism. Data were analyzed using a factor analysis tool through SPSS software. The results showed that there were 11 new factors formed from the point of view of archipelago tourists and 14 new factors formed from the point of view of foreign tourists so that there were differences between tourists in the practice of halal tourism.